IMPLEMENTASI PEMBELAJARAN TEMATIK KURIKULUM 2013 DALAM PEMBENTUKAN KARAKTER SISWA - Tetes Nur Sofiyatunningtiyas; Agung Nugroho; Arifin Muslim (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
Abstract. The ongoing curriculum 2013 is inseparable from strengthening the character. Strengthening character can be integrated through thematic learning carried out in class. The study aimed to describe the implementation of thematic learning based on 2013 curriculum in the context of building the characters of responsibility and teamwork on theme 9 for grade IV SD Negeri 1 Patikraja. This research implemented a qualitative approach with descriptive type. Data were obtained by observing, interviewing, and documenting. Data obtained were then analyzed through Miles and Huberman analysis model to draw conclusions. The results indicated that the implementation of character education consisted of integrating learning achievements in the form of planning, implementation and evaluation, educational institution synergize in strengthening character education, teacher competency strength and role models in implementing character education of responsibilities and teamwork. Supporting factors of the implementation in thematic learning were active students and teacher skills to build the character of children. The obstacles faced by teachers were limited facilities and infrastructure, time, student awareness and family factors. The solutions to overcome the obstacles were the teacher summarized the learning material, the teacher used the available facilities and infrastructure, the teacher approached the students with assistance and supervision, the teacher established good communication with studentsï¿½ parents.